Determinants Of Under-Five Mortality In Upper East Region Of Ghana: Evidence From Ghana Essential Health Intervention Program - Agula, M. (University Of Ghana, 2021)
Generally, the world has experienced a reduction in deaths below the age five in the past three decades. However, under-five mortality in low-income countries, including Ghana, is still very high. In Ghana, several programs, interventions and policies have been implemented which have led to a reduction in under-five mortality rates in the country. However, the rate of reduction will not meet Sustainable Development Goal 3.2, come 2030. The goal of this study is to examine the consistent drivers of children dying before age five over a period in the Upper East region of Ghana, using longitudinal data from the Ghana Essential Health Intervention Program (GEHIP). This longitudinal study compared baseline and end-line datasets collected in 2011 and 2015, respectively. Only data of children below five years were analysed for both the baseline and end-line surveys. Analytic data came from 3,422 and 2215 children below age five in the baseline and end-line surveys, respectively, all from mothers aged 15-49 years. Univariate, bivariate and multivariate analyses were conducted at different levels. At the univariate stage, descriptive statistics were generated to analyse the background characteristics of the sample. At the bivariate level, cross-tabulations were carried to determine the correlation between the independent variables and dying below the age five. Lastly, a multiple binary logistic regression model was fitted to determine the factors that consistently affect under-five child survival over time. Overall, results from the multivariate regression analysis suggest that breastfeeding and the number of vaccinations received by children were stable and significant determinants of under-five mortality over a period in the Upper East region, regardless of health system interventions. Baseline results show that breastfeeding, the number of vaccinations received at a particular stage of life of the child and the educational level of the mother were significantly associated with under-five mortality. For the end-line, the sex of the child, breastfeeding, sleeping under a treated bed net and the number of vaccinations received at a particular stage of life were significant determinants of under-five mortality. Findings suggest that parents of children should be educated on the benefits of adequate breastfeeding and urged to practice exclusive breastfeeding for improved health outcomes, including reducing under-five mortality. Also, postpartum care models by Ghana Health Service should pay particular attention to improving child immunization against childhood killer diseases.
M.A. Population Studies
Keywords: Mortality; Under-Five; Upper East Region; Ghana